“‘Tis still a dream, or else such stuff as madmen tongue and brain not.” Dream as performance in Cymbeline - Mike Nolan (Etudes Epistémè)
Posthumus’ dream in Shakespeare’s Cymbeline is significant in that it is a striking example of dream as performance. As he lies sleeping, Posthumus’ dream is fully enacted onstage so that the audience participates in the dreaming spectacle and is affected by, simultaneously with him, the instructive wonder of the experience. For Posthumus, the dream has a physical reality, for when he wakes, a tablet, given to him by Jupiter in his vision, has materialised. A cryptic inscription on the tablet marks the waking as a continuation of the dream process into the world of verifiable sensation. This article will consider the interaction of dream and performance, focusing especially on the role the senses play in describing and determining the experiential nature of the episode. It will also reference the Dreaming of Australian Aborigines as a means of interpreting the dream of Posthumus and examine the dramatic significance of the dream action in the course of the denouement of the play.